2011
DOI: 10.4049/jimmunol.1001139
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Switching in Ezrin Regulates Morphological and Cytoskeletal Changes Required for B Cell Chemotaxis

Abstract: B cell chemotaxis occurs in response to specific chemokine gradients and is critical for homeostasis and immune response. The molecular regulation of B cell membrane-actin interactions during migration is poorly understood. In this study we report a role for ezrin, a member of the membrane-cytoskeleton crosslinking Ezrin-Radixin-Moesin (ERM) proteins, in the regulation of the earliest steps of B cell polarization and chemotaxis. We visualized chemokine-induced changes in murine B cell morphology using scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 42 publications
2
66
3
Order By: Relevance
“…Several in vitro studies support the view that the presence of phosphomimetic ERM protein (ie, ERM protein unable to dephosphorylate) impairs lymphocyte migration. 9,17,18 However, apparently conflicting findings have been reported in 2 other studies. 15,16 Discrepancies between studies, which may reflect heterogeneity in cell types studied and in amounts of phosphomimetic ERM protein expressed, left ambiguity regarding the role of ERM protein phosphorylation in cell migration.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Several in vitro studies support the view that the presence of phosphomimetic ERM protein (ie, ERM protein unable to dephosphorylate) impairs lymphocyte migration. 9,17,18 However, apparently conflicting findings have been reported in 2 other studies. 15,16 Discrepancies between studies, which may reflect heterogeneity in cell types studied and in amounts of phosphomimetic ERM protein expressed, left ambiguity regarding the role of ERM protein phosphorylation in cell migration.…”
mentioning
confidence: 92%
“…12 They have been used in many biochemical and cell biologic studies of ERM protein activation/ function to probe the roles of ERM phosphorylation/dephosphorylation. 9,[13][14][15][16][17][18][19][20][21] For example, regulation of ERM protein phosphorylation has been implicated in functions as diverse as compaction in the mouse early embryo, 14 cell rounding in mitosis, 21 and promotion of uropod formation in lymphocytes. 15 Importance of regulated ERM protein phosphorylation in 1 or more of the events involved in lymphocyte recruitment from blood into tissue was suggested by findings that a key trigger of this process (chemokines) induced rapid dephosphorylation of ERM protein.…”
Section: Introductionmentioning
confidence: 99%
“…Such 'phosphocycling' of ezrin has recently been shown to be necessary for the formation of apical microvilli (Viswanatha et al, 2012). In fact, expression of the phosphomimetic ezrinT567D can lead to both loss and exaggerated stabilization of apical microvilli (Brown et al, 2003;Göbel et al, 2004;Parameswaran et al, 2011;Saotome et al, 2004). Many kinases have been reported to phosphorylate this site, and particularly strong evidence implicates SLK family kinases in both flies and mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning B cells migration, authors have shown that SWAP-70, a Rac-interacting protein involved in actin rearrangement (Pearce et al, 2006) and ezrin, a member of the membrane-cytoskeleton cross-linking ezrin-radixin-moesin proteins (Parameswaran et al, 2011) play important role during B cells chemotaxis. In addition, Rap-1 and -2 GTPases play an important role in mediating adhesion and cytoskeletal reorganization during SDF-1a-dependent B cell migration (McLeod et al, 2002;Durand et al, 2006;Chen et al, 2008).…”
Section: Actin Cytoskeleton Dynamics During Immune Cell Migration Andmentioning
confidence: 99%